2011
DOI: 10.1097/cnq.0b013e3182048073
|View full text |Cite
|
Sign up to set email alerts
|

“Scrub the Hub”

Abstract: This article reports the results of a study on the effect of alcohol disinfection duration on bacterial load on catheter hubs. Three different levels of disinfection (3, 10, and 15 seconds) were analyzed as well as a positive and negative control. All hubs with the exception of the negative controls were contaminated with a 10 bacterial solution and allowed to dry for 24 hours. Through each hub, 1 mL of sterile saline was flushed; a 10-μL calibrated loop was used to plate the flush onto blood agar. Colony coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…This confirms the absolute requirement to decontaminate injection ports of needle-free connectors when they are being accessed. However, there is conflicting opinion regarding whether a 5-second alcohol wipe of needle-free connectors is sufficient (Menyhay and Maki, 2006;Simmons et al, 2011;Rupp et al, 2012;Smith et al, 2012). As with the previous study (Casey et al, 2015) there was no significant difference between the median number of S. aureus recovered following a 5-or 15-second decontamination regimen (for each connector and overall).…”
Section: Discussionmentioning
confidence: 76%
“…This confirms the absolute requirement to decontaminate injection ports of needle-free connectors when they are being accessed. However, there is conflicting opinion regarding whether a 5-second alcohol wipe of needle-free connectors is sufficient (Menyhay and Maki, 2006;Simmons et al, 2011;Rupp et al, 2012;Smith et al, 2012). As with the previous study (Casey et al, 2015) there was no significant difference between the median number of S. aureus recovered following a 5-or 15-second decontamination regimen (for each connector and overall).…”
Section: Discussionmentioning
confidence: 76%
“…A Pennsylvania study reported that 71.7% (468/653) of central line infections occurred five days or more after insertion and may have been directly related to use and care of intravascular devices [ 60 , 108 110 ]. Contamination of the catheter directly through the catheter hub has been confirmed through published studies [ 12 , 13 , 111 – 113 ]. These studies found that bacteria identified on external hub surfaces were also present in biofilm sampled from random locations within the needless connector.…”
Section: Introductionmentioning
confidence: 76%
“…Rupp demonstrated 5 second alcohol disinfection was effective; this was in direct contrast with the Smith study where contact time of 10/12/15 seconds was deemed adequate, but 5 and 8 seconds were not as effective to prevent bacterial transfer [ 170 , 171 ]. Simmons and colleagues found 3/10/15 seconds significantly decreased the bacterial load in an in vitro laboratory study, with some level of bacteria remaining during all duration levels tested; disinfection failed to completely eliminate contaminants [ 13 ]. More studies are needed to provide efficacy for optimal time necessary to eliminate surface contaminants.…”
Section: Resultsmentioning
confidence: 99%
“…There are likely several contributing factors to the decrease in GNR bacteremia events after 2009 in this population. Several infection control interventions were implemented between 2009 and 2010, including the initiation of chlorhexidine gluconate (CHG) baths in January 2010, the development and implementation of a new line bundle also in January 2010, adoption of “scrub the hub” 21 as a standardized protocol in September 2010, and a switch to CHG impregnated dressings in February 2009. Since such interventions have been associated with decreased rates of bloodborne infections, 2224 it is possible that together, they contributed to the decrease in GNR bacteremia between 2009 and 2012.…”
Section: Discussionmentioning
confidence: 99%